Como as características da paisagem e rodovia explicam atropelamentos em áreas protegidas à escala local? - Freitas, Nayara Helena Alecrim de (2015)
The implementation of paved or rural roads, cause significant changes both in the landscape and in biodiversity. Roadkill is seen as the major impact of roads to many species of vertebrates and invertebrates. Although work out different factors that influence mortality from trampling, such as road width, speed and vehicle traffic, weather, landscape, animal biology and consciousness of the driver, few highlight the importance of these factors on a local scale. Therefore, monitoring was carried out in close proximity or internal roads to protected areas, the Atlantic Forest and Brazilian Cerrado, recording the coordinates and surrounding pictures of all the non-flying wild vertebrates run over. The goal was to detect landscape characteristics and road that influence us run over on a local scale not seen in methods addressed in most studies of this issue for amphibians, reptiles and mammals. We build mixed generalized linear models to understand the relationship of the landscape and road to the occurrence of roadkills. For landscape characteristics, our study found that air connectivity was a positive factor significantly in amphibians. Regarding to the road characteristics, the presence of structures, on one or both sides of the road, that difficult the animals passage and paved slopes were the most important factors significantly increase mortality in amphibians. In reptiles, the presence of the shoulder, on one or both sides of the road, roadkill significantly decreased for that class. These information can assist the government and concessionaires in decision making to mitigate roadkills.